Role of amoebae for survival and recovery of 'non-culturable' Helicobacter pylori cells in aquatic environments. Issue 10 (8th September 2020) - Dey, Rafik; Rieger, Aja; Banting, Graham; Ashbolt, Nicholas J
ABSTRACT: Helicobacter pylori is a fastidious Gram-negative bacterium that infects over half of the world's population, causing chronic gastritis and is a risk factor for stomach cancer. In developing and rural regions where prevalence rate exceeds 60%, persistence and waterborne transmission are often linked to poor sanitation conditions. Here we demonstrate that H. pylori not only survives but also replicates within acidified free-living amoebal phagosomes. Bacterial counts of the clinical isolate H. pylori G27 increased over 50-fold after three days in co-culture with amoebae. In contrast, a H. pylori mutant deficient in a cagPAI gene ( cagE ) showed little growth within amoebae, demonstrating the likely importance of a type IV secretion system in H. pylori for amoebal infection. We also demonstrate that H. pylori can be packaged by amoebae and released in extracellular vesicles. Furthermore, and for the first time, we successfully demonstrate the ability of two free-living amoebae to revert and recover viable but non-cultivable coccoid (VBNC)- H. pylori to a culturable state. Our studies provide evidence to support the hypothesis that amoebae and perhaps other free-living protozoa contribute to the replication and persistence of human-pathogenic H. pylori by providing a protected intracellular microenvironment for this pathogen to persist in natural aquatic environments and engineered water systems, thereby H. pylori potentially uses amoeba as a carrier and a vector of transmission. Abstract : Free-living amoebae were shown to play a role in the survival and recovery of H. pylori in aquatic environments, demonstrating a new mechanism for their distribution and persistence in these habitats.